If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -8 = 8 Reorder the terms: -8 + -1x = 8 Solving -8 + -1x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1x = 8 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = 8 + 8 -1x = 8 + 8 Combine like terms: 8 + 8 = 16 -1x = 16 Divide each side by '-1'. x = -16 Simplifying x = -16
| 32t+72=40 | | 2.3=C-3 | | 12-x=-5x+16 | | 6k=-4k+5k | | c^2-11c+30= | | (5-3x)-(-4x+-6)=(8x+11)-(3x-6) | | 5=16x-3 | | -21/3-(-5) | | 1/2(8-6h) | | 5x+3=-44 | | 9g+7=-29 | | p+6.9=-7.6 | | 2r-(-6)=10 | | 5x+(-32)=18 | | -17=11+4x | | r-5=12 | | 7a+(-21)=0 | | 152=19x | | -8-8(-2n-1)=-112 | | -8-2x=-12 | | 4=n-14 | | 5+3(q-4)=5q+1 | | 3t+13=-11 | | 5x-25=2x+114 | | 18-3r=24 | | 5-7n+2n=-2n+2n | | 9y-(-22)=58 | | n-11=68 | | -11h-7=-18 | | 20x+10x=180 | | 4x^2-x+15=0 | | n-8=75 |